Survival benefit of overweight patients undergoing MitraClip® procedure in comparison to normal‐weight patients. Issue 12 (7th September 2022) - Keller, Karsten; Geyer, Martin; Hobohm, Lukas; Tamm, Alexander R.; Kreidel, Felix; Ruf, Tobias F.; Hell, Michaela; Schmitt, Volker H.; Bachmann, Kevin; Born, Sonja; Schulz, Eberhard; Münzel, Thomas; et al.
Abstract: Background: The number of MitraClip® implantations increased significantly in recent years. Data regarding the impact of weight class on survival are sparse. Hypothesis: We hypothesized that weight class influences survival of patients treated with MitraClip® implantation. Methods: We investigated in‐hospital, 1‐year, 3‐year, and long‐term survival of patients successfully treated with isolated MitraClip® implantation for mitral valve regurgitation (MR) (June 2010–March 2018). Patients were categorized by weight classes, and the impact of weight classes on survival was analyzed. Results: Of 617 patients (aged 79.2 years; 47.3% females) treated with MitraClip® implantation (June 2010–March 2018), 12 patients were underweight (2.2%), 220 normal weight (40.1%), 237 overweight (43.2%), and 64 obesity class I (11.7%), 12 class II (2.2%), and 4 class III (0.7%). Preprocedural Logistic EuroScore (21.1 points [IQR 14.0–37.1]; 26.0 [18.5–38.5]; 26.0 [18.4–39.9]; 24.8 [16.8–33.8]; 33.0 [25.9–49.2]; 31.6 [13.1–47.6]; p  = .291) was comparable between groups. Weight class had no impact on in‐hospital death (0.0%; 4.1%; 1.5%; 0.0%; 7.7%; 0.0%; p  = .189), 1‐year survival (75.0%; 72.0%; 76.9%; 75.0%; 75.0%; 33.3%; p  = .542), and 3‐year survival (40.0%; 36.8%; 38.2%; 48.6%; 20.0%; 33.3%; p  = .661). Compared to normal weight, underweight (hazard ratio [HR]: 1.35 [95% confidence interval [CI]: 0.65–2.79], p  = .419), obesity‐class I (HR: 0.93 [95% CI: 0.65–1.34], p  = .705), class II (HR: 0.39 [95% CI: 0.12–1.24], p  = .112), and class III (HR: 1.28 [95% CI: 0.32–5.21], p  = .726) did not affect long‐term survival. In contrast, overweight was associated with better survival (HR: 1.32 [95% CI: 1.04–1.68], p  = .023). Conclusion: Overweight affected the long‐term survival of patients undergoing MitraClip® implantation beneficially compared to normal weight. Abstract : Long‐term survival stratified for weight classes illustrated by Hazard plot for patients treated with MitraClip® implantation stratified for weight classes. Association of weight class compared to normal‐weight with long‐term survival (adjusted for Logistic EuroScore). Survival rate at discharge, 1‐year follow‐up, and 3‐year follow‐up stratified for weight classes.